2011
DOI: 10.1519/jsc.0b013e3181e07585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wearing a Cooling Vest During the Warm-Up on 10-km Run Performance

Abstract: The purpose of this study was to examine whether wearing a cooling vest during an active warm-up would improve the 10-km time trial (TT) performance of endurance runners. Seven male runners completed 3 10-km TTs (1 familiarization and 2 experimental) on a treadmill after a 30-minute warm-up. During the warm-up of the experimental TTs, runners wore either a t-shirt (control [C]) or a cooling vest (V), the order of which was randomized. No differences were found between the C and V conditions for the 10-km TT ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 16 publications
2
33
2
Order By: Relevance
“…However, in their study, Quod et al (2008) removed the cooling vest before the 20-min warm-up, which may have reduced the efficacy of PC on the TT performance. Also, despite comparable durations of PC during the warm-up, our results differ from those of Stannard et al (2011), who reported no effect of wearing a cooling vest before 40-min running exercise in warm conditions. The greater thermal stress imposed in our study (35°C vs~25°C in Stannard et al (2011)), as well as the ice vests' cooling efficiency may explain this difference (Ross et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in their study, Quod et al (2008) removed the cooling vest before the 20-min warm-up, which may have reduced the efficacy of PC on the TT performance. Also, despite comparable durations of PC during the warm-up, our results differ from those of Stannard et al (2011), who reported no effect of wearing a cooling vest before 40-min running exercise in warm conditions. The greater thermal stress imposed in our study (35°C vs~25°C in Stannard et al (2011)), as well as the ice vests' cooling efficiency may explain this difference (Ross et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with some (Johnson et al, 2008;Bogerd et al, 2010), but not all (Quod et al, 2008;Stannard et al, 2011) studies, the present results showed that ice vest PC improved 20-km TT performance in the heat. While the 4.4% increase in PO observed in the current study is similar to the 5.2% improvement during a 20-km TT reported by Johnson et al (2008), Quod et al (2008) only reported a 1.5% improvement in similar environmental and self-paced exercise conditions to the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The purpose of precooling is to lower Tc before starting the exercise, leading to an increase in heat storage capacity during exercise. It is hypothesised that the larger heat buffer, induced by precooling, enables the body to perform more work prior to reaching a critical limit for Tc 13. This suggests that precooling and percooling enhance exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…All participants had a minimum of 5 days of recovery between each visit. To eliminate any bias, participants were informed that the study aimed to investigate whether running in a cooling vest either improved performances because of cooling, or decreased performances because of the added weight of the vest [ 27 ] . All visits were scheduled between 9:00 a.m. and 6:00 p.m. To minimize the eff ects of the circadian rhythm on the T c and heart rate [ 2 , 34 ] , the time trial tests were performed at the same time of the day for each subject.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade many cooling techniques were evaluated in athletes, with particular interest in precooling strategies [ 21 ] . Precooling increases the heat storage capacity of the body which enables an athlete to perform more work before reaching limiting T c levels, thus delaying the onset of fatigue due to hyperthermia [ 27 ] . Precooling with cold air, cold water immersion, cooling vests, ice slurry ingestion and combinations Exercise-induced increase in core body temperature may lead to the development of hyperthermia ( > 40.0 °C) and/or decreased performance levels.…”
mentioning
confidence: 99%